2021
DOI: 10.1016/j.resourpol.2020.101898
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 drives connectedness among commodity and financial markets: Evidence from TVP-VAR and causality-in-quantiles techniques

Abstract: With many commodity and financial markets reportedly experiencing poor performances during this COVID-19 pandemic, this study intends to examine the effect of the pandemic on the connectedness among the markets. There are several reasons that suggest that apart from the pandemic affecting the performances of the markets, it can also be a driver of their connectedness, coming from the perspective of the global financial cycle channel. Therefore, we first employ the recently developed time-varying parameter vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
111
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(139 citation statements)
references
References 112 publications
11
111
0
2
Order By: Relevance
“…As documented in Table 1 (Panel B), EMVID causes all the connectedness measures except the net directional connectedness of China and Hong Kong. Nevertheless, we cannot rely on the result of the linear causality test due to the possibility of poor performance in the presence of undesirable statistical properties and nonlinearities (see, Adekoya & Oliyide, 2020;Balcilar et al, 2016;Fasanya et al, 2021). With this in mind, we proceed to performing the Brook et al (BDS test, 1996), which can unveil the presence of nonlin-Uncertainty Due to Pandemic and the Volatility Connectedness Among Asian REITs Market earities among the series.…”
Section: Causality Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…As documented in Table 1 (Panel B), EMVID causes all the connectedness measures except the net directional connectedness of China and Hong Kong. Nevertheless, we cannot rely on the result of the linear causality test due to the possibility of poor performance in the presence of undesirable statistical properties and nonlinearities (see, Adekoya & Oliyide, 2020;Balcilar et al, 2016;Fasanya et al, 2021). With this in mind, we proceed to performing the Brook et al (BDS test, 1996), which can unveil the presence of nonlin-Uncertainty Due to Pandemic and the Volatility Connectedness Among Asian REITs Market earities among the series.…”
Section: Causality Testsmentioning
confidence: 99%
“…In this vein, we motivate our study in three ways. First, the COVID-19 pandemic, which has its origin from the Asian-Pacific region (Akinsomi, 2020), has been noted as having a significant influence on the global REITs market (Akinsomi, 2020), and other financial markets, causing them to be volatile and subtle to shocks (Adekoya & Oliyide, 2020;Iyke, 2020aIyke, , 2020b. Second, Liow & Huang (2018) document that the volatility transmission between international REITs' is sensitive to crises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line of research, Mazur et al ( 2020 ) found that natural gas, healthcare, software, and food stocks earn high positive returns, whereas, petroleum, entertainment, real estate, and hospitality sectors stocks fall dramatically during the COVID-19 pandemic. Adekoya and Oliyide ( 2021 ) and Gorbel and Jeribi ( 2021b ) show that the latter cited pandemic is responsible for risk transmission across commodity and financial markets. Contrary to gold, Ghorbel and Jeribi ( 2021b ) found that Bitcoin cannot be considered as a safe haven during the global pandemic when investing in crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…As research in the healthcare perspective is starting to yield significant effects, it is now time to focus our attention on the economy and the significant consequences the pandemic has had in this context. A number of scholars have already studied the impact of the global health crisis on financial markets whose sharp fluctuations during the pandemic have led to confusion and uncertainty among investors [ 14 , 15 , 16 ]. Results reported by other researchers indicate that the SARS-CoV-19 pandemic has changed consumer behaviors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%